A recurrent missense mutation in the EDAR gene causes severe autosomal recessive hypohidrotic ectodermal dysplasia in two consanguineous Kashmiri families - Sadia (2021)
Background: Hypohidrotic ectodermal dysplasia (HED) is a rare congenital disorder arising from the abnormal development of ectoderm derived structures, including skin, hair, nails, teeth and glands. These patients have sparse hair on the whole body, including the scalp, as well as hypoplastic teeth. They have no resistance to heat as a result of abnormal sweat glands. In total, four genes, namely ectodysplasin A (EDA), ectodysplasin A receptor (EDAR), EDAR‐associated death domain protein (EDARADD) and Wnt family member 10A (WNT10A), are known to be involved in the etiology of HED. Methods: In the present study, we investigated two consanguineous Kashmiri families (A &B) with an autosomal recessive form of HED. Using whole exome sequencing and different bioinformatics tools, we detected a recurrent mutation causing severe HED. Results: We identified an already known rare homozygous missense (NM_022336 c.1300 T>C; p.W434R; minor allele frequency 0.00007) variant in exon 12 of the EDAR gene. This variant segregated with a homozygous form in all patients and their obligate carriers were heterozygous. A panel of > 100 unrelated ethnically matched controls was screened, and the mutation was not identified outside the families. Furthermore, the candidate variant is predicted to be damaging by in silico software giving a CADD (Combined Annotation Dependent Depletion) score of 25.5, which indicates that the variant is among the top 1% of the deleterious variants in the human genome. Conclusions: The identification of the same homozygous mutation segregating with disease in two different families supports the important role of the gene in the development of the disorder and this may contribute to novel approaches, prenatal diagnosis and genetic counseling of families with EDAR related disorders.